Insights Into the Pathogenesis of Bullous Pemphigoid: The Role of Complement-Independent Mechanisms - Cole, Connor; Vinay, Keshavamurthy; Borradori, Luca; Amber, Kyle T. (Frontiers in Immunology, 2022)
Bullous pemphigoid is an autoimmune blistering disease caused by autoantibodies targeting BP180 and BP230. While deposits of IgG and/or complement along the epidermal basement membrane are typically seen suggesting complement -mediated pathogenesis, several recent lines of evidence point towards complement-independent pathways contributing to tissue damage and subepidermal blister formation. Notable pathways include macropinocytosis of IgG-BP180 complexes resulting in depletion of cellular BP180, direct induction of pro-inflammatory cytokines from keratinocytes, as well as IgE autoantibody- and eosinophil-mediated effects. We review these mechanisms which open new perspectives on novel targeted treatment modalities.